SELF-FINANCING CAPACITY AND TAXATION INFLUENCE ON FIRM PROFITABILITY - Daniela SIMTION (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper deals with the influence of taxes on the company’s profitability and self-financing capacity, presenting a case study. Taxes are being defined as sampling of a part of the income or wealth of a person. Based on the data collected from the Balance Sheet and Profit and Loss Account, the self-financing capacity of the firm was determined by two methods: the deductive method and the additional method. The self-financing capacity of SC ALFA CONSTRUCT S.R.L. registered an increasing trend in the analyzed period. Thus, in 2015, it reached Lei 1,105,443, being by 33.76 times higher than in 2013. As a conclusion, considering the influence of taxation on certain economic and financial performances we get to the following reality: taxation can be a determining factor in decision-making at enterprise level.